Energy analysis study of coal tar distillation process by feed splitting method - Wahyudi Eko Pratomo; Sri Agustina; Teguh Kurniawan (Jurnal Teknika, 2021)
Coal tar is a high viscosity liquid and has a black color which formed as a by-product of the production process of coke and gas from coal. Coal tar compounds have high economic value because they can be resold and valuable. One valuable compound is naphthalene. The coal tar evaluation process of its constituent components is carried out by distillation, with a high level of naphthalene purity achieved up to 96%. The coal tar distillation process normally requires high energy, which leads to expensive operational costs.  In order to achieve low energy consumption during the distillation process,  a study of energy analysis in the coal tar distillation process needs to be done. This study aims to analyze the energy consumption of the distillation process by using simulator software. Process simulations will be performed using the Aspen HYSYS simulator, where the variable in the form of the ratio of the feed flow rate into the distillation tower is divided into two streams, namely cold stream and hot stream. The location of the changed input feed is also a changing variable in this study. The fixed variables in this study were the operating conditions of the distillation process and the incoming feed flow rate, which was 2 m3/hour. The simulations suggest that the amount of energy saved in the condenser unit is 4.40 percent and 5.28 percent in the reboiler unit. Tar batubara adalah cairan dengan viskositas tinggi dan berwarna hitam, hasil samping dari proses produksi kokas dan gas dari batubara. Senyawa tar ini memiliki nilai ekonomi yang tinggi karena komponen-komponen penyusunannya dapat dijual kembali dan bernilai, salah satunya adalah naftalena. Proses pemisahan tar batubara dari komponen-komponen penyusunnya dilakukan dengan cara destilasi, dengan tingkat kemurnian naftalena yang tinggi yaitu 96%. Proses destilasi tar batubara ini seringkali membutuhkan energi yang besar, sehingga kajian mengenai analisa konsumsi energi pada proses destilasi tar batubara perlu dilakukan. Studi analisa energi pada proses destilasi tar batubara dilakukan dengan menggunakan metode simulasi proses. Simulasi proses destilasi dilakukan dengan menggunakan perangkat lunak berupa Aspen HYSYS, dimana variabel yang berupa ratio laju alir umpan masuk ke dalam menara destilasi dibagi menjadi 2 aliran, yaitu aliran dingin dan aliran panas. Letak umpan masuk yag dirubah juga merupakan variabel berubah pada penelitian ini. Variable tetap pada penelitian ini adalah kondisi operasi proses destilasi dan laju alir umpan masuk, yaitu 2 m3/jam. Hasil dari simulasi yang telah dilakukan didapatkan besarnya energi yang dapat dihemat sebesar 4.40% pada unit condenser dan 5.28% pada unit reboiler.